Shared Decision-Making Is Associated with Better Outcomes in Patients with Knee But Not Hip Osteoarthritis: The DECIDE-OA Randomized Study. (5th January 2022) - Sepucha, Karen R.; Vo, Ha; Chang, Yuchiao; Dorrwachter, Janet M.; Dwyer, Maureen; Freiberg, Andrew A.; Talmo, Carl T.; Bedair, Hany
Abstract : Background: Current guidelines recommend shared surgical decision-making, yet it is unclear whether shared decision-making improves health outcomes in patients who are considering knee and hip replacement. The purpose of the present study was to examine whether patients who made high-quality, informed, patient-centered (IPC) decisions had better health outcomes, higher satisfaction, and less decision regret compared with those who made lower-quality decisions. Methods: A multisite, randomized study of 2 decision aids for patients with hip and knee osteoarthritis was utilized to collect data on decision-making and health outcomes at 2 time points: shortly after the initial surgical evaluation and about 6 months after treatment. We calculated the percentage of patients who made an IPC decision and examined the a priori hypotheses that IPC decisions would be associated with better health outcomes, satisfaction, and less regret at 6 months. Linear and logistic regression models were utilized to examine the relationships. Results: The analytic sample included 854 patients with a mean age of 65 years (standard deviation, 9 years), of whom 58% were female, 93% were White non-Hispanic, 67% had knee (compared with hip) osteoarthritis, and 62% underwent operative treatment within 6 months of the initial evaluation. The majority of patients (68%) made IPC decisions. The IPC group had significantly larger gains in quality of life (mean difference in EuroQol-5 Dimension, 0.04; 95% confidence interval [CI], 0.02 to 0.07; p < 0.001) compared with the non-IPC group. For knee patients, the IPC group also had significantly better Knee injury and Osteoarthritis Outcome Scores (mean difference, 4.9; 95% CI, 1.5 to 8.3; p = 0.004), higher satisfaction (adjusted odds ratio [aOR], 1.7; 95% CI, 1.2 to 2.3; p = 0.003), much better pain relief (aOR, 2.1; 95% CI, 1.3 to 3.5; p = 0.002), and were more likely to have no decision regret (aOR, 2.3; 95% CI, 1.3 to 4.1; p = 0.003). For hip patients, IPC decisions were not associated with better Harris hip scores or satisfaction and were associated with more regret. Conclusions: Higher-quality decisions predicted small improvements in health outcomes, as well as greater satisfaction and less regret for patients with knee osteoarthritis, but not for patients with hip osteoarthritis. Level of Evidence: Therapeutic Level II . See Instructions for Authors for a complete description of levels of evidence.